Trends in IT: The Media Switchover Dilemma - Rao, M. Jagan Mohan; Annapurna, B.; Babu, K.H.; Sehgal, R.N. (DESIDOC Journal of Library & Information Technology, 2003)
Many Libraries and lnformation Centres aH over the world are facing the dilemma of striking a balance between the age ldp rint media and new electronic media. An experiment run in the United States during 1991-95 under code name 7ULlP' and the 'CORE' project based at the Cornell University, US, provide insights into the issue and facilitate the resolution of the dilemma. The salient findings of these experiments and the likely shape the search for online information rnay take are briefly discussed. http://dx.doi.org/10.14429/dbit.18.5.3411